2021
DOI: 10.3390/v13010142
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Super-Resolution Imaging of T-Cell Plasma Membrane CD4 Redistribution upon HIV-1 Binding

Abstract: The first step of cellular entry for the human immunodeficiency virus type-1 (HIV-1) occurs through the binding of its envelope protein (Env) with the plasma membrane receptor CD4 and co-receptor CCR5 or CXCR4 on susceptible cells, primarily CD4+ T cells and macrophages. Although there is considerable knowledge of the molecular interactions between Env and host cell receptors that lead to successful fusion, the precise way in which HIV-1 receptors redistribute to sites of virus binding at the nanoscale remains… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Here we describe for the first time that OCLN recruitment correlates with HCV particle stabilization at the plasma membrane, a mechanism employed by viruses to be efficiently internalized (15). Indeed, clustering viral receptors for efficient internalization is a relevant concept that has previously been demonstrated for other viruses, including the human immunodeficiency virus (HIV), dengue virus (DENV), transmissible gastroenteritis virus (TGEV) and the canine parvovirus (CPV) (42)(43)(44)(45). Interestingly, while HCV is probably one of the viruses to which the greatest number of entry factors has been attributed to, very little is known about HCVreceptor dynamics.…”
Section: Discussionmentioning
confidence: 95%
“…Here we describe for the first time that OCLN recruitment correlates with HCV particle stabilization at the plasma membrane, a mechanism employed by viruses to be efficiently internalized (15). Indeed, clustering viral receptors for efficient internalization is a relevant concept that has previously been demonstrated for other viruses, including the human immunodeficiency virus (HIV), dengue virus (DENV), transmissible gastroenteritis virus (TGEV) and the canine parvovirus (CPV) (42)(43)(44)(45). Interestingly, while HCV is probably one of the viruses to which the greatest number of entry factors has been attributed to, very little is known about HCVreceptor dynamics.…”
Section: Discussionmentioning
confidence: 95%
“…T cell activation through the TCR leads to clustering of signaling proteins 39 and single-molecule imaging experiments have shown that both CD4 and Lck can form small, nanoscale clusters within minutes of triggering 40,41 , in part through confinement in CD2 nanodomains 42 . To compare the population-level clustering of CD4 and Lck ( i.e ., integrated over all positions in all cells) we compared the brightness values generated from sFCS as a measure of molecular oligomerization 23 ( Figure 5d ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to targeting membrane structure, disruption of the lateral organization of the host cell membrane has also proven to be a valid antiviral strategy. Because, as exposed above, clustering of CD4 and coreceptors seems to be a key requisite for effective infectivity, [56][57][58] alteration of receptor lateral diffusion by increasing ceramide levels in the membrane hamper receptor and coreceptor engagement and HIV-1 fusion. [33,163,164] Similarly, chol-binding antibodies also seem to alter lateral membrane organization of the host cell, hampering interaction between Env and receptor and coreceptors.…”
Section: Targeting Viral or Host Cell Membranes To Prevent Viral Entrymentioning
confidence: 99%
“…[ 56,57 ] In addition, this clustering seems to be enhanced after binding HIV‐1 Env, increasing the size of the clusters 3‐ to‐10‐fold. [ 58 ] Indeed, depletion of cholesterol (chol) from the target cell membranes significantly impairs viral entry, [ 21 ] presumably by impeding CD4 localization to these domains and disrupting the receptor clusters necessary for efficient fusion. [ 59,60 ] Interestingly, while the CCR5 coreceptor also seems to be at least in part associated with raft, [ 59 ] the CXCR4 coreceptor seems to surround these membrane nanodomains but to be itself localized mainly into non‐raft domains.…”
Section: Viral Attachmentmentioning
confidence: 99%